2009
DOI: 10.1002/lapl.200910057
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Mathieu-Gauss mode oscillation in micro-grained Nd:YAG ceramic lasers with azimuth laser-diode pumping

Abstract: Mathieu-Gauss mode oscillations were observed in micro-grained isotropic Nd:YAG microchip ceramic lasers with azimuth laser diode pumping. The effect of fluorescence anisotropy or thermal birefringence on these pattern formations is discussed for several laser materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…[48][49][50][51][52][53][54][55][56] A number of publications appeared also on generation of the so-called cylindrical vector (cv) modes, which correspond to solutions of the wave equation in the vector form in cylindrical coordinates. Due to the large number of potential applications, there has been an increasing interest in studying methods of generation of different laser modes having circularly symmetric geometry, namely cylindrical scalar or vector LG and BG modes.…”
Section: Introductionmentioning
confidence: 99%
“…[48][49][50][51][52][53][54][55][56] A number of publications appeared also on generation of the so-called cylindrical vector (cv) modes, which correspond to solutions of the wave equation in the vector form in cylindrical coordinates. Due to the large number of potential applications, there has been an increasing interest in studying methods of generation of different laser modes having circularly symmetric geometry, namely cylindrical scalar or vector LG and BG modes.…”
Section: Introductionmentioning
confidence: 99%
“…[3]. Alvarez-Elizondo et al and Tokunaga et al were both directly observed lasing MGMs in different laser systems [4][5]. In this study, we drafts simulation code to model the optical filed oscillation of end-pumped solid-state lasers, and proposed a kind of axicon-based stable laser resonator.…”
Section: Introductionmentioning
confidence: 90%
“…The laser-oscillation simulation model adopted in this study is based on Endo's simulation method [8][9], which can simulate a single-wavelength, single/multi-mode oscillation in unstable/stable laser cavities. This code was recently used to demonstrate selecting a single Ince-Gauss mode pattern, using azimuthal tight focus pumping [5]. As Fig.…”
Section: Description Of the Simulation Approachmentioning
confidence: 99%
“…The investigations on the optical properties and laser performance of anisotropic Nd:YAG ceramics have already showed it would be an excellent candidate like Nd:YAG crystal that was extensively used in laser [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%